A new species of Friesea (Collembola: Neanuridae) from the Antarctic Continent. Issue 33 (10th September 2018) - Greenslade, Penelope
ABSTRACT: A new species of Friesea was found in East Antarctica and is described here as Friesea eureka sp. nov. This is the first new collembolan species to be described from the Antarctic continent in 30 years, even though ice-free areas have been intensively surveyed over that time. It brings to five the number of described species of the genus Friesea known from the Antarctic continent and Peninsula, so is the most speciose genus of Collembola in the region. However, one of these, F. grisea Schäffer, comprises a number of cryptic species of different molecular lineages. The new species is distinguished by having 4 + 4 ocelli plus 1 + 1 hardly visible, a very reduced furca, up to four or five faintly clavate tenent hairs, four anal spines and four spinose chaetae in adult. The restricted distribution of the species emphasises the importance of protecting ice-free areas on the continent as they often contain at least one locally endemic faunal species www.zoobank.org/urn:lsid:zoobank.org:pub:865B9AE6-0428-4364-99A4-AF38A764D6D9